Level- and sport-specific Star Excursion Balance Test performance in female volleyball players - Vitale, J. A.; Vitale, N. D.; Cavaleri, L.; Dazzan, E.; Lombardi, G.; Mascagni, P.; La Torre, A.; Banfi, G. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Investigations of Star Excursion Balance Test (SEBT) performance differences between competition levels and sports are limited and results are inconsistent. The aim of the present study are: 1) to compare SEBT performance between elite and semi-professional female volleyball players; 2) to evaluate differences in SEBT scores between positions (Hitters, Middle Blockers, Setters, and Liberoes); and 3) to compare dynamic balance characteristics between professional female Italian volleyball players with NCAA Division I female athletes practicing six different sports (hockey, football, basketball, golf, softball, and volleyball). For the latter comparison, previously published data obtained from a study were used. METHODS: Fifty-one female volleyball players were grouped in two groups, elite athletes (EG; N.=27) and semi-professional players (SG; N.=24), and further categorized into hitters, middle blockers, setters, and liberos. Anterior (A), posteromedial (PM), and posterolateral (PL) distances, and composite score (COMP) of SEBT short form were studied. COMP was calculated as the average of the normalized distances across the three directions. RESULTS: Significant differences were observed for the A (right, P=0.014 and left, P=0.011), PL (right, P=0.017 and left, P=0.008), PM (P<0.001) directions, and COMP scores (right, P=0.008 and left, P=0.009), with higher normalized distances noted for the EG and no differences between different positions. COMP scores were lower for the EG than the NCAA Division I female hockey (P<0.001) and football players (P=0.031) but similar to those of basketball, golf, softball, and volleyball players. CONCLUSIONS: The EG scored higher on dynamic postural-control tasks than the SG. SEBT performance varied significantly between sports. Clinicians and strength coaches need to be aware of sport specific differences in dynamic postural control measurements in both rehabilitation and athletic development.